Dividend Policy and Stock Price Volatility: A Case of Nepalese Commercial Banks - Sharma, Nishchal; Poudel, Dilip; Ghalan, Juliya; Khadka, Kamana; Sah, Kanchan; Shahi, Mohin (Nepalese Journal of Business, 2025)
The study examines the effect of dividend policy on stock price volatility of Nepalese commercial banks. The dependent variables selected for the study are stock price volatility and change in market price per share. The selected independent variables are dividend yield, dividend payout, bank size, earnings per share, leverage and return on equity. The study is based on secondary data of 10 commercial banks with 108 observations for the study period from 2013/14 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB), Economic Survey Report published by Ministry of Finance and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of dividend policy on stock price volatility of Nepalese commercial banks. The study showed that dividend yield has a negative effect on stock price volatility and change in market price per share. It means that increase in dividend yield leads to decrease in stock price volatility and change in market price per share. Similarly, dividend payout has a positive effect on stock price volatility and change in market price per share. It means that increase in dividend payout ratio leads to increase in stock price volatility and change in market price per share. The results of the study also showed that bank size has a positive effect on change in market price per share. It implies that increase in bank size leads to increase in change in market price per share. Likewise, earnings per share have a positive effect on stock price volatility which indicates that higher earnings per share leads to increase in stock price volatility. However, leverage ratio has a negative effect on stock price volatility. It implies that higher leverage ratio leads to decrease in change in market price per share. Similarly, return on equity has a positive effect on stock price volatility. It implies that higher return on equity leads to increase in stock price volatility.